Análisis documental sobre la investigación en educación para la democracia en Colombia: Una apuesta para la construcción de cultura política en la última década del siglo XX y principios del siglo XXI, a partir de estudios en educación para la democracia en la escuela. (Papeles, 2011)
This article seeks to explain some experiments, carried out between the 90 and the first decade of the century, which account for the exercise of democratic culture in the school, and their role in building the political culture within the same, based on studies from developed research, analysis of the proposals set out by the Ministry of Education and whose framework massive test design based on national and international standards, which can be extensive use of quantitative methodologies and approaches psicologicistas, privileged by the tendency of civic political culture, and that would be part of the so-called analysis of official pedagogic discourse agenciamiento. On the other hand, there are the studies that have been concerned about visible in the strategies designed to measure from the Constitution, the Education Act and Decree 1860 have influenced the consolidation of democratic culture within the school environment, from the same foundational processes such as participation, cooperation, coexistence, conflict, regulations, among others, defining the construction (or not) of new meanings and subjectivities against public intervention in the educational institution by the school actors. These studies thus show a tendency to be a qualitative and ethnographic.